Flowing water makes me never forget: Memories of Khmer Pop Music in the Cambodian American Diaspora - DeMatteo, Bradley. (Tufts University. Tisch Library., 2019)
In the Cambodian American community of Lowell, Massachusetts-home to the second largest Cambodian population in the U.S.-the sounds of the past are alive in the present. In local clubs, businesses, and family homes, one is likely to encounter the pop music of 1950s-1975 Cambodia. Jomreang pe'dam, "the songs from the beginning" as this genre is referred to in Khmer, peaked in the years following Cambodian independence from France in 1953, and thrived until the Khmer Rouge genocide from 1975 to 1979. In both Lowell and Cambodia, jomreang pe'dam historically index this tumultuous and deeply traumatic period of the recent past. However, due to their sustained presence in Cambodian social life, the old songs simultaneously represent Khmer cultural heritage, continuity, and survival. This thesis explores jomreang pe'dam in the present-day Cambodian American diaspora as archival, reflexive, and variable means of accessing Cambodian cultural and autobiographical memories.; Thesis (M.A.)--Tufts University, 2019.; Submitted to the Dept. of Music.; Advisor: Richard Jankowsky.; Committee: Stephanie Khoury, and Rabbi Jeffrey Summit.; Keywords: Music, Social research, and Southeast Asian studies.